Pengaruh Pengawasan Keuangan Daerah, Akuntabilitas, dan Transparansi Pengelolaan Keuangan Daerah Terhadap Kinerja Pemerintah Daerah Pada Kabupaten Aceh Barat Daya - Fifit Purnama; Nadirsyah Nadirsyah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this research is to examine the influence of local finance supervision, accountability, and local finance management transparency of the performance of local government of South-West Aceh (Abdya) regency. Population of the research is 44 SKPK (SatuanKerjaPerangkatKabupaten). The sampling technique used was simple random sampling, 31 SKPK were selected a the sample of the research with 93 respondents in total. The data used in the supervision sectorewere quantitative types and the data resource was primary resource. The data was collected using questionnaire. The data was analyzed using multiple regression analysis aided by SPSS program of version 20.00.The result showed that the supervision of the local finance, accountability, and transparency in the finance management either simultaneously or partially influence the performance of the local government of Abdya regency.Keywords : Supervision , Accountability , Transparency , Local Government Performance